PENGARUH TABUNGAN MUDHARABAH, PEMBIAYAAN MUDHARABAH-MUSYARAKAH DAN PENDAPATAN OPERASIONAL LAINNYA TERHADAP LABA STUDI PADA BANK JATIM SYARIAH PERIODE 2007-2015 - Purwaningsih, Farida (IAIN Tulungagung, 2016)
The research aims to examine the infuence of savings of Mudharabah, fnancing of Mudharabah-Musharaka and other operating incomes in increasing the proft of Bank Syariah Jatim. The method of analysis in this research used analysis of double linear regression. Populations in the research are the fnancial report of Bank Syariah Jatim. The results of research showed that the profts will increase as savings of Mudharabah increase. In fnancing of Mudharaba-Musharaka, it happened inversely; when fnancing declined, the proft would increase. It happened because the fnancing which attracted by many customers are the ones with the principle of murabaha fnancing. While, other operational will affect the increase of profts. When other operating incomes increased, the proft would also increase. In the contrast, other operating incomes decreased, the earned proft also would decrease. If all these variables are maximized in its operations, it would assist in increasing the profts at Bank Syariah Jatim.Keywords: Savings of Mudharabah, Financing of Mudharabah-Musharaka, Other Operating Incomes, Proft